Safety assessment of the ethanolic extract from Piper vicosanum yunck leaves in male rats - Bárbara Campos Jorge (Elsevier, 2022)
Background: Piper vicosanum (Piperaceae) is a species used in folk medicine mainly due to its anti-inflammatory and analgesic properties. However, the data available about its safety are still insufficient. Purpose: This study evaluated the toxicological profile and reproductive impacts in male rats treated with the ethanolic extract from Piper vicosanum leaves (EEPV) during a 28-day treatment. Methods: Male Wistar rats received ethanol extract of EEPV (0, 100, 200, or 300 mg/kg) by gavage for 28 consecutive days. Results: Males treated with EEPV did not exhibit clinical signs of toxicity during the treatment. Although hematological parameters were unaltered, a decrease in AST, total proteins, alkaline phosphatase and creatinine levels was observed in the treated animals. However, no evidence of histological changes was found in the liver and kidney. EEPV also induced an increase of abnormal sperm in males. Conclusion: The prolonged use of ethanolic extract of Piper vicosanum leaves affected biochemical and sperm parameters, showing that care should be taken when it is used for prolonged periods. Further studies, including a 90-day toxicity assay, should be performed.